Evaluation of the safety and feasibility of electrochemotherapy with intravenous bleomycin as local treatment of bladder cancer in dogs - Rangel, Marcelo Monte Mor; Linhares, Laís Calazans Menescal [UNESP]; de Oliveira, Krishna Duro; Suzuki, Daniela Ota Hisayasu; Maglietti, Felipe Horacio; de Nardi, Andrigo Barboza [UNESP] (Springer Nature, 2023)
Local treatment of canine urothelial carcinoma (UC) of the bladder is a challenge. More than 90% of the cases invade the muscular layer, more than 50% develop on bladder sites with a difficult surgical approach and often requiring radical surgical procedures. This study aims to evaluate the safety and feasibility of electrochemotherapy (ECT) with intravenous bleomycin (BLM) as a local therapy for bladder UC. This prospective study included 21 dogs with spontaneous bladder UC. Regional/distant metastases and neoplastic infiltration of the serosa was considered the main exclusion criteria. We had no deaths during ECT or in the immediate postoperative period, and no suture dehiscence. Most dogs (19/21) developed mild adverse effects, whereas two dogs developed ureteral stenosis. Complete response (CR) was achieved in 62% of the cases (13/21), while partial response (PR) was achieved in 24% (5/21). The median survival and disease-free survival times were 284 and 270 days, respectively. Overall survival was significantly better in the dogs who achieved a CR. In conclusion, ECT was well-tolerated in dogs with UC, demonstrating its safety and feasibility. These data pave the way for new studies aimed at evaluating the effectiveness of ECT in canine bladder UC as a translational model for human disease.